2003
DOI: 10.1093/ajcn/78.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fatty acid composition and depression are associated in the elderly: the Rotterdam Study

Abstract: In community-dwelling persons, fatty acid composition is related to depression. Because this relation was not secondary to inflammation, atherosclerosis, or possible confounders, it suggests a direct effect of fatty acid composition on mood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
3
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(148 citation statements)
references
References 34 publications
9
131
3
5
Order By: Relevance
“…The participants' characteristics are summarized in Table 1. The scores (mean7SD) on the eight scales of the SF-36 were [8,32]. Table 2 shows the results of the hierarchical linear regression analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants' characteristics are summarized in Table 1. The scores (mean7SD) on the eight scales of the SF-36 were [8,32]. Table 2 shows the results of the hierarchical linear regression analyses.…”
Section: Resultsmentioning
confidence: 99%
“…It has often been suggested that long-chain polyunsaturated fatty acids (LCPUFA), which are primarily found in fish, may lower the risk of developing depressive symptoms [7][8][9]. Strikingly, the relationship between LCPUFA status and quality of life has scarcely been investigated-only one study has addressed this issue to date.…”
Section: Introductionmentioning
confidence: 99%
“…(1998) (63) C major depression (64) C major depression (65) C major depression (66) C and SC major depression (67) C major depression in ACS patients (68) C major depression in ACS patients (69) C depression in MI patients (70) C postpartum (71) C major depression (72) C major depression (74) NC adolescent depression (75) NC depression in lung cancer patients…”
Section: Trial Evidencementioning
confidence: 99%
“…Many studies have found lower LCn3PUFA levels in erythrocyte membranes [28], total serum [29], plasma [43] and plasma phospholipids [30,44] in depressed patients and inverse relationships between these LCn3PUFA biomarkers and depression status, while others have found no such relationships [42,[45][46][47]. These discrepancies may be due to differing demographic characteristics of the samples evaluated (including severity of depressive symptoms), type of cardiovascular disease, the method of depression measurement and the component of blood extracted for the assessment of LCn3PUFA content.…”
Section: Discussionmentioning
confidence: 99%